Principles of Neurorehabilitation After Stroke Based on Motor Learning and Brain Plasticity Mechanisms - Maier, Martina; Ballester, Belén Rubio; Verschure, Paul F. M. J. (Frontiers in Systems Neuroscience, 2019)
Neurorehabilitation addresses the question of whether recovery can occur after a brain injury like a stroke and how this recovery process could be optimized. Instead of teaching compensatory strategies that do not reduce impairment but allow the patient to return home as soon as possible, functional recovery might be more sustainable as it ensures a long-term reduction in impairment and an improvement in quality of life. Neuroscience sheds light on the mechanisms of learning new functions or relearning lost ones. The aim of neurorehabilitation is to exploit interventions based on human and animal studies about motor learning and to show that the activation of experience-dependent neuronal plasticity augments functional recovery. At the same time, neurorehabilitation permits the scientific community to collect valuable data, which allows inferring about the functionality and connectivity of the brain. However, current rehabilitation methods lack the exact operationalization of evidence gained from motor learning literature, leading to an urgent need to bridge motor learning theory and present clinical work in order to identify a set of ingredients and practical applications that could guide future interventions. This work aims to unify the neuroscientific literature relevant to the recovery process and rehabilitation practice in order to provide a synthesis of the principles that constitute an effective neurorehabilitation approach. Previous attempts to achieve this goal either focused on a subset of principles or did not link clinical application to the principles of motor learning and recovery. We identified 15 principles of motor learning based on existing literature: massed practice, spaced practice, dosage, task-specific practice, goal-oriented practice, variable practice, increasing difficulty, multisensory stimulation, rhythmic cueing, explicit feedback/knowledge of results, implicit feedback/knowledge of performance, modulate effector selection, action observation/embodied practice, motor imagery, and social interaction. We comment on trials that successfully implemented these principles and report evidence from experiments with healthy individuals as well as clinical work.